Harmonization of Contents the Draft Regional Regulation on Financial Management of Gorontalo Province - Igirisa, Siti Rahmawaty; Insani, Nur; Marwan, Marwan (Amsir Law Journal, 2023)
The formation of regional regulations cannot be separated from the harmonization of draft regional regulations. This stage is carried out to avoid overlapping regional regulations, in the sense that these regional regulations do not conflict with higher or equivalent laws and regulations, both vertically and horizontally, as well as aspects of content and finishing techniques. This research is a normative legal that examines the harmonization of the contents of the regional regulation draft regarding the financial management of the Gorontalo Province. The results of the study illustrate that the preparation of laws and regulations must refer to a philosophical basis, namely legal norms which are based on legal ideals (rechtsidee) as the highest legal value, then on a sociological basis which has a high level of effectiveness towards society, and then on a juridical basis which must be based on higher regulatory norms. Furthermore, in harmonizing the contents of the draft regional regulation on the financial management of the Gorontalo Province, it was seen that there was a significant gap, including the improvement of the preamble formulation, the legal basis for consideration, the addition of articles governing the regional regulations of the Gorontalo Province regarding regional financial management. The current regional regulation status is an implementing regulation in the form of a Governor’s Regulation, as the executor of this regional regulation. ___ References Books with an author: Efendi, Jonaedi., and Ibrahim, Johnny. (2018). Metode Penelitian HukumNormatif dan Empiris. Depok: Prenadamedia Group. Irwansyah. (2021). Penelitian Hukum: Pilihan Metode & Praktik Penulisan Artikel. Yogyakarta: Mirra Buana Media. Journal articles: Arifin, M. Y. R. (2019). Perekonomian Nasional Dalam Perspektif Undang-Undang Dasar 1945 Negara Republik Indonesia. Celebes Equilibrum Journal, 1(1), 26-31. Basyir, A. (2014). Pentingnya Naskah Akademik Dalam Pembentukan Peraturan Perundang-Undangan Untuk Mewujudkan Hukum Aspiratif Dan Responsif. Jurnal IUS Kajian Hukum dan Keadilan, 2(5), 285-306. Bunga, M. (2020). Model Pembentukan Peraturan Daerah yang Ideal Dalam Penyelenggaraan Otonomi Daerah. Jurnal Hukum & Pembangunan, 49(4), 818-833. Cerdas, F. A., Abdurahman, A., and Perwira, I. (2022). Harmonisasi dalam Proses Pembentukan Peraturan Daerah di Indonesia. Jurnal Ilmu Hukum Kyadiren, 4(1), 40-53. Elcaputera, A. (2022). Urgensi Harmonisasi Rancangan Peraturan Daerah: Sebuah Analisis Tantangan dan Strategi Pembentukan Peraturan Perundang-undangan Indonesia dalam Rangka Penguatan Otonomi Daerah. Jurnal Ilmu Hukum, 11(1), 121-136. Gusman, D., Alsyam, A., and Nazmi, D. (2021). Pelaksanaan Peran Kantor Wilayah Kementerian Hukum Dan Ham Sumatera Barat Dalam Rangka Harmonisasi Peraturan Daerah Provinsi Sumatera Barat Tahun 2019. UIR Law Review, 5(2), 68-79. Huzaeni, M. R., and Firdausiah, N. (2022). Inefisiensi Peraturan Daerah di Indonesia. Rechtenstudent Journal UIN KHAS Jember, 3(1), 42-55. Marwan, M., and Insani, N. (2022). Kedudukan Hukum Pengelolaan Tanah Wakaf oleh Nazhir di Kecamatan Dungingi Kota Gorontalo. Al-'Aqdu: Journal of Islamic Economics Law, 2(1), 12-24. Noerdin, Z., Libra, R., and Syahputra, R. O. (2022). Pelaksanaan Pengharmonisasian dan Pemantapan Konsepsi Rancangan Peraturan Daerah Kota Pekanbaru Berdasarkan Undang-Undang Nomor 15 Tahun 2019 Tentang Perubahan Atas Undang Undang Nomor 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang-Undangan. Jurnal Hukum Respublica, 21(2), 221-229. Nugroho, M. O., Burlian, P., and Huzaimah, A. (2021). Kewenangan Pemerintah Daerah dalam Pengharmonisasian, Pembulatan, dan Pemantapan Konsep Raperda Provinsi Pasca Lahirnya UU No. 15 Tahun 2019 tentang Perubahan Atas UU No. 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan. Jurnal Komunikasi Hukum (JKH), 7(2), 759-778. Nuradhawati, R. (2019). Dinamika Sentralisasi dan Desentralisasi di Indonesia. Academia Praja: Jurnal Ilmu Politik, Pemerintahan, dan Administrasi Publik, 2(01), 152-170. Rukmanda, M. A., and Prasetyoningsih, N. (2021). Pengharmonisasian Materi Muatan dalam Pembentukan Peraturan Daerah Penyertaan Modal Badan Usaha Milik Daerah. Media of Law and Sharia, 3(1), 40-58. Sianturi, H. (2017). Kedudukan Keuangan Daerah Dalam Pengelolaan Dana Hibah dan Bantuan Sosial Berdasarkan Perspektif Keuangan Negara. Jurnal Wawasan Yuridika, 1(1), 86-105. Syaputra, M. Y. A. (2016). Kajian Yuridis terhadap Penegasan Hiearaki Peraturan Perundang-Undangan di Indonesia dalam Perspektif Stufen Theorie. Jurnal Mercatoria, 9(2), 95-103. Tamimu, A. R. (2019). Pembatalan Peraturan Daerah Menurut Undang-Undang Nomor 9 Tahun 2015 tentang Perubahan Kedua Atas Undang-Undang Nomor 23 Tahun 2014 tentang Pemerntah Daerah. Lex Administratum, 7(2), 90-97. Taufiqurrahman, M. (2019). Peran Perancang Peraturan Perundang-Undangan Kementerian Hukum dan Hak Asasi Manusia dalam Pengawasan Produk Hukum Daerah Melalui Executive Preview. Soumatera Law Review, 2(2), 270-281. Wicaksono, D. A., and Rahman, F. (2020). Penafsiran terhadap Kewenangan Mengatur Pemerintahan Daerah dalam Melaksanakan Urusan Pemerintahan melalui Pembentukan Peraturan Daerah. Jurnal Negara Hukum, 11(2), 231-248.